2021
DOI: 10.1111/ijcs.12701
|View full text |Cite
|
Sign up to set email alerts
|

Consumption practices during the COVID‐19 crisis

Abstract: This research draws on protection motivation theory, temporal construal theory, and self‐determination theory to understand consumption practices during a pandemic crisis by looking at the narratives of British consumers during the COVID‐19 crisis. A two‐stage design is adopted: the first stage adopts an exploratory strategy to identify consumption‐related themes using netnography, while the second stage explores these themes further to gain a deeper insight through 13 semi‐structured interviews. Three themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 105 publications
4
113
0
2
Order By: Relevance
“…To cope with risk perceptions to foodborne illnesses, consumers today by and large more demand locally harvested food, organic food, sustainable agricultural products (Birch et al., 2018; Shahabi Ahangarkolaee & Gorton, 2021; Yoo et al., 2015); however, all of these product claims are only evidenced to consumers by traceability tools. In particular, the effects of the Covid‐19 pandemic have visibly altered the food habits of the people on the earth (Gordon‐Wilson, 2021; Lacombe et al., 2021), thus, not only healthy eating but food safety are also much higher centered than ever for the sake of health protection. Inevitably, food purchasers will become informed and conscious consumers in the coming years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To cope with risk perceptions to foodborne illnesses, consumers today by and large more demand locally harvested food, organic food, sustainable agricultural products (Birch et al., 2018; Shahabi Ahangarkolaee & Gorton, 2021; Yoo et al., 2015); however, all of these product claims are only evidenced to consumers by traceability tools. In particular, the effects of the Covid‐19 pandemic have visibly altered the food habits of the people on the earth (Gordon‐Wilson, 2021; Lacombe et al., 2021), thus, not only healthy eating but food safety are also much higher centered than ever for the sake of health protection. Inevitably, food purchasers will become informed and conscious consumers in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars can carry out some systematic—approached studies to determine factors impacting consumer switching decisions for food‐safety choices by incorporating other theoretical research frameworks such as the Antecedents—Decision—Outcome (ADO) model (Paul & Benito, 2018) or the Motivation—Opportunity—Ability (MOA) model (Maclnnis et al., 1991). In the current time, several studies posit that consumer's behavior will be changed dramatically due to profound influences of the COVID‐19 pandemic (Eger et al., 2021; Gordon‐Wilson, 2021; Lacombe et al., 2021; Prentice et al., 2020); hence, studies on food consumption in the post‐pandemic stage should be timely elaborated to triviliate a better understanding of consumer switching decisions. In the same vein, future studies drawing on the PPM perspectives can invigorate the predictive power of this theoretical model by explicitly investigating effects of social factors (i.e., social influences, social presence…), environmental factors (i.e., food security, ethical consumption, sustainability incentives…) rather than solely personal factors on consumer's switching decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are needed to explore the change in perceived xenophobia and resultant acculturative stress before and after the pandemic. Studies have also shown an increase in panic buying (i.e., buying in excess in the fear of going out of stock; Prentice et al., 2020) and indulgent buying behavior (e.g., consumption of alcohol, unhealthy snack; Gordon‐Wilson, 2021a, 2021b) amid the pandemic. These studies imply that there is a correlation between stress and panic or indulgent buying.…”
Section: Discussionmentioning
confidence: 99%
“…(Baran, 2021;Campbell, Inman, Kirmani, & Price, 2020;Finsterwalder, Kabadayi, Fisk, & Boenigk, 2021;Giroux et al, 2021;Gordon-Wilson, 2021;Itani & Hollebeek, 2021;Kim, Yang, Min, & White, 2021;Kirk & Rifkin, 2020;Lim, 2021;Milakovic, 2021;Nayal, Pandey, & Paul, 2021;Nofiani, Indarti, Lukito- Budi, & Manik, 2021;Racat, Capelli, & Lichy, 2021;Toubes, Araujo Vila, & Fraiz Brea, 2021;Zwanka & Buff, 2021). (Ardanza-Ruiz & Lavin, 2021; Baarsma & Groenewegen, 2021; Cox et al, 2020; do Amaral Moretti, da Silva Gabriel, do Prado, & Alcantara Fagundes, 2021; Ellison, McFadden, Rickard, & Wilson, 2021; Goolsbee & Syverson, 2021; Gupta, Simon, & Wing, 2020; Im, Kim, & Choeh, 2021; Pantano et al, 2020; Pantano, Priporas, Devereux, & Pizzi, 2021; Paul, Menzies, Zutshi, & Cai, 2020; Rejeb,Rejeb, & Keogh, 2020;Safara, 2021;Veselovska, Zavadsky, & Bartkova, 2021;Zhang, Liu, & Yao, 2021) (Barnes, Diaz, & Arnaboldi, 2021;Billore & Anisimova, 2021;Garner, Safir, & Schild, 2020;Hall, Fieger, Prayag, & Dyason, 2021;Kaur & Malik, 2021;Kazancoglu & Demir, 2021;Loxton et al, 2020;Musyaffi, Sari, & Respati, 2021;Oana, 2020;Pham et al, 2020;Prentice, Chen, & Stantic, 2020;Prentice, Nguyen, et al, 2021;Prentice, Quach, & Thaichon, 2021;Tan, Sia, & Tang, 2021)…”
mentioning
confidence: 99%